2020
DOI: 10.1039/d0ra08970b
|View full text |Cite
|
Sign up to set email alerts
|

A simplified approach for the metal-free polymerization of propylene oxide

Abstract: Mild organobases and Et3B constitute an operationally simple, user-friendly catalyst setup for polymerizing propylene oxide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 32 publications
0
22
0
Order By: Relevance
“…In some cases, triethylborane was added as a cocatalyst, which accelerates monomer consumption and facilitates the preparation of very long PPO blocks (Scheme ). For synthetic details, please refer to the Experimental Section and the SI.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In some cases, triethylborane was added as a cocatalyst, which accelerates monomer consumption and facilitates the preparation of very long PPO blocks (Scheme ). For synthetic details, please refer to the Experimental Section and the SI.…”
Section: Resultsmentioning
confidence: 99%
“…This approach is based on the tailored synthesis of so-called “Reverse Pluronics” with high molar masses, preparation of which is enabled by recent advances in polymerization catalysis. Notably, the synthesis of these polyether SDAs can be conducted with fully commercially available and cheap catalyst setups . Combined with the facile carbon material synthesis, which is based on literature precedent and in every aspect a standard procedure, it is hoped to herewith deliver a user-friendly tool for rapid OMC screening.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the organocatalyzed ROP of epoxides has advanced significantly in recent years, these organocatalysts cannot overcome the dominance of the metal-based catalysts in terms of cost and catalytic performance . However, a fully commercially available catalyst setup of organoboron and organobases has displayed strong competitiveness with metallic catalysts in producing polyethers …”
Section: Dinuclear Organoboron Catalysts For Rop Of Epoxidesmentioning
confidence: 99%
“…[21][22] This borane can be employed together with a range of organobases, including very simple nitrogen bases. 23 Intriguingly, elegant work by Zhao and Ling has demonstrated that with such a setup even poly(ester-ether) multiblock motifs can be constructed -excessive transesterification is avoided during growth of the polyether blocks. 24 What deserves particular attention is the proposed mechanism, which necessitates two equivalents of Et3B per organobase, a stoichiometry inherently linked to the simultaneous monomer activation and chain-end deactivation/coordination, which is also well-known from Lewis-pair polymerization (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%